2003
DOI: 10.1038/sj.eye.6700374
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of open-angle glaucoma in Iceland: Reykjavik Eye Study

Abstract: Purpose To establish the age-and sex-specific prevalence of open-angle glaucoma (OAG) subsuming pseudoexfoliation (PEX) in the city of Reykjavik. Methods Participants 50 years of age and older who were part of the Reykjavik Eye Study and classified as having glaucoma were divided into three categories: Category 1: two or more of the following based on optic nerve stereophotograph reading: vertical cup to disc ratio (VCDR) 97.5th percentile (40.7), focal glaucomatous disc change, C/D asymmetry of 97.5th percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
1
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 24 publications
(28 reference statements)
13
84
1
8
Order By: Relevance
“…110,155,161,196,203 The six studies reported that 6126 (97.1%) of 6308 participants provided interpretable test results for NCT, while one prospective cohort study 211 involving 105 participants reported that all provided interpretable test results, giving an overall rate of 97.2% for all studies. One study reported that it took approximately 2 minutes to perform the test for both eyes.…”
Section: Interpretable Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…110,155,161,196,203 The six studies reported that 6126 (97.1%) of 6308 participants provided interpretable test results for NCT, while one prospective cohort study 211 involving 105 participants reported that all provided interpretable test results, giving an overall rate of 97.2% for all studies. One study reported that it took approximately 2 minutes to perform the test for both eyes.…”
Section: Interpretable Resultsmentioning
confidence: 99%
“…Only A-rated studies are described in this section (n = 19). 21,22,28,63,64,99,[105][106][107][108][109][110][111][112][113][114][115][116][117] All but one of the included studies 105 described a population-based cross-sectional study. The remaining eight studies [100][101][102][103][104][118][119][120] are also described in Appendix 6.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations